Analisis Performa dan Karakteristik Emisi Gas Buang Motor Bensin Dari Penggunaan Bahan Bakar Campuran Plastic Oil-Pertalite - sunaryo, Sunaryo (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2020)
Plastic waste is a potential alternative energy source. The purpose of this study was to analyze the characteristics of plastic oil (plastic oil) and analyze thermal efficiency, specific fuel consumption and exhaust emissions of gasoline engines by using alternative fuels resulting from pyrolysis of plastic waste. Plastic oil (PO) is produced through the pyrolysis process using raw materials from Low-density Polyethylene (LDPE) plastic types and is mixed with pertalite gasoline with a volume ratio of 10% (PO10), 20% (PO20) and 30% (PO30). The characteristics of the plastic oil mixture are tested for their properties, while the performance and exhaust emissions testing are carried out with a dynamometer and engine gas analyzer on a single-cylinder gasoline motor. The results showed that the characteristics of plastic oil mixtures have properties that are identical to gasoline fuels. The motor performance test found that the maximum power and torque achieved from the PO-pertalite fuel mixture was slightly lower than gasoline, where the PO10 power reduction was 4.8%, PO20 was 6.0% and PO30 was 6.0%, while the magnitude of torque reduction for PO10 was 0.7 %, PO20 of 2.1% and PO30 of 4.5%. For thermal efficiency (Î®th) there was also a decrease, namely PO10 by 1.5%, PO20 by 2% and PO30 by 3.5%. Related to the specific fuel consumption (SFc) proven PO-pertalite mixture shows more economical results than pertalite gasoline. In addition, the level of exhaust emissions also shows a decrease in HC, CO, O2 and increasing CO2 as an additional percentage of PO in gasoline. These results indicate that pyrolysis oil plastic waste is a promising alternative fuel to be applied to gasoline engines.